"Greener" adhesives composed of urea-formaldehyde resin and cottonseed meal for wood-based composites. (20th June 2018) - Liu, Ming; Wang, Yan; Wu, Yiqiang; He, Zhongqi; Wan, Hui
Abstract: Urea-formaldehyde (UF) resin is one of the most widely used adhesives in wood-based composites. The major concerns of the resin utilization are free formaldehyde release and poor water resistance. In this study, based on life cycle assessment (LCA) analysis, a "greener" adhesive composed of UF resin and cottonseed meal was successfully prepared via a common synthetic process of pure UF resins. The raw materials (urea and formaldehyde) of UF resins were replaced by cottonseed meal with up to 40% on weight basis. The effect of the cottonseed meal on the rheological property, mechanical strength, chemical structure, thermal stability, and glue line features of these "greener" adhesives was investigated. The adhesive showed an improved mechanical strength as compared to pure UF resins in the tensile shear strength of bonded wood specimens, especially on the water soaked strength. It also showed similar chemical structures, thermal stabilities, and even better rheological properties than pure UF resins. Cottonseed meal resulted in good dispersions in these adhesives with up to 30% portion. It acted as a reinforcement for the adhesive other than a filler or an additive. This "greener" adhesive improved the performance of pure UF resins while retained its outstanding features, suggesting the feasibility of using it as UF resins in current manufacturing lines for wood-based composites is there. Graphical abstract: Image Highlights: "Greener" adhesives composed of UF resin and cottonseed meal were formulated via a typical UF resin synthetic process. Raw chemical materials in pure UF resin could be replaced by cottonseed meal with up to 40% on weight basis. The "greener" adhesive shows better performance than UF resin in aspects of water resistance, rheological properties, etc. These "greener" adhesives are suitable, at least, for replacing UF resins in wood-based composites manufacturing while retaining its low cost.